(untitled) (Research, Society and Development, 2020)
The first infection caused by the new coronavirus occurred in China in December 2019. Since then, the search for COVID-19 treatment has become the target of international research. Although studies began shortly after the viral outbreak in China, publications of these studies were expected to increase worldwide after the World Health Organization’s statement on the pandemic state of the disease. Thus, this study aimed to analyze the dynamics of scientific publications on the treatment of COVID-19 in the first half of 2020. For data collection, the MEDLINE platform was used through PubMed; the descriptors adopted were: "COVID-19 and Treatment" and "SARS-CoV-2 and Treatment", restricting the publication period from 01/01/2020 to 30/06/2020. Data showed that in January 2020, the initial phase of the pandemic, the number of publications on the subject was small compared to June, with the pandemic totally disseminated. The largest increase in the number of publications occurred between February and March (8.3 times higher). Regarding the number of countries involved in publications, it is observed that in January, three countries were involved; while in May there were 41 countries. In the period analyzed, China led with 152 publications, followed by the United States (141). This may be the result of the emergence of the first cases of the disease and the socioeconomic character of both, which despite the different political regimes, have scientific research as an important point for the continuity of development.